Stratifikasi Vegetasi Di Beberapa Taman Publik Kota Surabaya Pada Analisa Kemampuan Simpanan Karbon Dalam Menyerap Gas Emisi Karbondioksida - Ni Putu Devina Putri Maharani; Tuhu Agung Rachmanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Global warming has become a serious problem in our environment in recent years. The purpose of this study was to analyze carbon stocks in several public parks in the city of Surabaya so as to reduce emissions produced in Bungkul Park, Prestasi Rungkut Kidul Park, and Bratang Flora Park. storing the highest carbon reserves, namely Pterocarpus indicus, Ceiba pentandra, and Cerbera manghas with carbon stock values of 225.28 kg/month, 82.62 kg/month and 76,194 kg/month. The estimated emission of carbon dioxide (CO2) gas, which originating from the use of LPG, electricity consumption, and the need for motorized vehicle fuel (BBM) was carried out by observing 3 locations namely those in Darmo Village, Barata Jaya Village, and Rungkut Kidul Village. Darmo Urban Village CO2 emissions resulting from household activities such as the use of LPG is 1.32 tons COzeq/month, 1.22 tons COzeq/month and 0.37 tons COzeq/month, from the use of fuel for daily transportation activities of 0.47 tons COzeq month, and from electricity usage of 22.86 tons COzeq/month in the settlement sector is very good so that it can reduce global warming that is happening in the city of Surabaya.Keywords: emissions, public parks, carbon storage, biomassa